Preparation Of Live Attenuated Vaccine Against Strangles: M. M. Kaisium , A.M.H. AL- Judi - Kaisium, M. M. (The Iraqi Journal of Veterinary Medicine, 2007)
Live attenuated vaccine of Strept. Equi was prepared by culturing the bacteriumin increasing concentration of acriflavin and the vaccine was given byinstallation in the nose of rabbits. The treated group showed immune response,the titer of the antibodies was 59.4 ± 4.57 after 2 weeks of vaccination, 237±18.28 after 4 weeks, 475.4 ± 36.57 after 6 weeks, & reach atiter of 512 ± 0 after8 weeks, and the treated group did not show any signs after challenge dose,while the control group died after challenge.